Hubungan Antara Kecerdasan Spiritual Dengan Solidaritas Mekanik Umat Beragama (Studi Kasus Di Desa Karangsari, Kec. Cluwak, Kab. Pati, Jawa Tengah) - Sutrisno Sutrisno; Jeny Harianto; Jo Priastana (Dhammavicaya : Jurnal Pengkajian Dhamma, 2021)
Research on the relationship between spiritual intelligence and the mechanical solidarity of religious people (Case Study inNgawen Village, Cluwak District, Pati Regency, Central Java) is important research for the development of religious life inIndonesia. That is because, the appreciation of religion is something that accompanies religious life, but at the same timereligion also requires a strong bond of brotherhood. This study tries to look at the relationship between the individual andsocial dimensions of religious life. This study discusses the discussion of spiritual intelligence with the mechanicalsolidarity of Buddhists in Karangsari Village, Kec. Cluwak, Kab. Starch. Obtained from ex-post facto research because thefacts or symptoms that were collected already existed before the respondent or symptoms appeared without the presence ofconsultation. The data in this study were obtained based on respondents' answers in the questionnaire research. Datacollected includes ordinal data. This data refers to the resolution or classification of responses to instrument approval. Thisresearch proves that there is no difference between Spiritual Intelligence and Mechanical Solidarity. Based on dataprocessing, the results of the relationship between the two variables are positive, but in the low category. The lowrelationship between Spiritual Intelligence and Mechanical Solidarity can be interpreted as Buddhist social piety, not fullyrelying on the internal values of Buddhism. However, awareness can be determined by values and norms that are giventogether. The facts that occur in the field can show a phenomenon that is getting stronger and closer, the social ties ofsociety, the deeper the religious feelings and the feelings about the sacred things that accompany each manifestation aregathered.